Prospects for the management of diabetic neuropathy - Alexandr Sergeevich Ametov; Marina Alexandrovna Lysenko (Сахарный диабет, 2011)
Diabetic peripheral neuropathy (DPN) is one of the most common chronic complications of diabetes mellitus leading to deterioration of the patientsquality of life. Effective methods for the treatment of DPN and improvement of both quality of life and long-term prognosis of the disease remain tobe developed.To review pathogenetic mechanisms of DPN, the known methods of DPN treatment and the influence of activation of PPAR-alpha receptors onpathogenesis and outcome of DPN.